Mobile Phone Base Stations Health Effects - A. Alazawi , Shahab (Diyala Journal of Medicine, 2019)
Background: The rapid increase of mobile telephony and the associated obvious presence of mobile phone base stations have raised concerns about possible non specific health symptoms (NSHS) caused by emitted microwaves, electromagnetic field (EMF), radiofrequency (RF) and radiofrequency electromagnetic radiations (RFR) Aims: To investigate the health effects among the residence proximity to mobile phone base station in Baquba city. Materials and Methods: A cross-sectional study from May 2010 till June 2010 of randomly selected inhabitants living in Baquba urban areas for more than one year near to (8 )selected base stations, (375) subjects (200 women and 175 men) were investigated and completed standardized questionnaires that focused on the relevant parameters. Result: The results of the questionnaire survey reveal that people living in the vicinity of base stations report various complaints frequencies, Chi-square with Yates correction were used in relation to the sex, age and distance from mobile base stations, show significant (p <0.05) increase as compared to people living >300 m or not exposed to base stations. In relation of sex; women complained mostly of nausea, headaches, men complain mostly of lowering of libido. In relation to age, in subjects older than 19 years, this study shows the existence of a greater sensibility for some NSHS symptoms such as headaches, fatigue, sleep disturbances, irritability, feeling of discomfort, dizziness, cardiovascular problems when comparisons are made between subjects living up to 300 m vs. subjects of the reference group. In relation to distance, the complaints are experienced in a significantly higher (p <0.05) by the subjects in the distance zones of < 10 m to 300m from base stations. Up to10m the symptoms are headaches, sleep disturbances, irritability, depressive tendencies, feeling of discomfort, loss of appetite, nausea, difficulties in concentration, , visual disturbances, lowering of libido. Significant differences (P < 0.05) are observed up to 100 m from base stations for symptoms such as: headaches sleep disturbances, irritability, depressive tendencies, feeling of discomfort, difficulties in concentration, memory loss and lowering of libido. In the zone 100 m to 200 m from base stations, the symptoms of headaches, sleep disturbances, feelings of discomfort, feeling of discomfort, difficulties in concentration, memory loss are again experienced significantly more often(P<0.05) in comparison with the reference group. Beyond 200 m only the symptom of headaches, fatigue, sleep disturbances is reported at a significantly high frequency (P < 0.05). There was significant increase in the prevalence of sleep disturbance, fatigue, feeling of discomfort among the inhabitants opposite to the station (20.8% versus 10.9%, 23.4% versus 9.8%, 26.0% versus 12.0%) (P < 0.05) respectively. Conclusions: This study shows that inhabitants living nearby mobile phone base stations are at risk for developing non specific health symptoms, the facing position appears to be the worst one for distances from cellular phone base stations < 100 m, so more research concerning the effects of radiofrequency radiation from base stations is indicated. It is advisable that cellular phone base stations should not be sited closer than 300 m to populations, as a precautionary measure, sitting of base stations should be such as to minimize exposure of neighbors. Recommendations: Revision of standard guidelines for public exposure to RER from mobile phone base station antennas, regular assessment and early detection of biological effects among inhabitants around the stations are recommended.